(untitled) (Open International Journal of Informatics, 2023)
At present, people in the countryside use a manual agricultural machine for harvesting. This contributes to global warming and agricultural safety problems as manual irrigation increases farmers’ time on the farm. The use of manual machinery causes smoke during irrigation, which increases the heating of the earth’s surface and thus reduces the green energy effect. So they do not spend a lot of money on buying crude oil when they use the system. On the other hand, there are bandits who come into conflict with farmers and animals that attack farmers in the bush, which makes it difficult for farmers to reach their farms. A simple but effective IoT system, as we have proposed in this study, helps to solve these problems to a large extent. In this study, we use a combination of a Raspberry Pi as the main processor and sensor modules as devices to collect agricultural data for further insights and analysis. Apart from automatic irrigation through the power-saving water pump, the developed systems have taken the initiative to reduce the time farmers have to spend on the farm and provide instant notifications to a mobile device at any time and place.